1979
DOI: 10.1113/jphysiol.1979.sp012635
|View full text |Cite
|
Sign up to set email alerts
|

Sodium and calcium fluxes in a clonal nerve cell line.

Abstract: SUMMARY1. 22Na+ and 45Ca2+ fluxes were studied in the clonal nerve cell line PC12. Three distinct types of ion channels were found: (a) voltage-dependent Na+ channels, (b) voltage-dependent Ca2+ channels, and (c) acetylcholine-activated channels permeable to both ions.2. 22Na+ uptake through voltage-dependent Na+ channels is induced by veratridine and scorpion venom, and is inhibited 50 % by 5 x 10-7 M-tetrodotoxin and greater than 98 % by 5 x 106 M-tetrodotoxin.3. o*Ca2+ uptake through voltage-dependent Ca2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
1
2

Year Published

1980
1980
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(81 citation statements)
references
References 45 publications
4
74
1
2
Order By: Relevance
“…Part of this discrepancy between adrenaline output and level of depolarization may be due to the Ca permeability of the ACh receptor channel (Douglas, Kanno & Sampson, 1976b;Douglas & Rubin, 1963). If this is the case then this is in contrast to results obtained from an adrenal chromaffin cell line where stimulation of catecholamine secretion (Ritchie, 1979) by cholinergic agonists is predominantly due to Ca influx through the voltage dependent Ca channel (Stallcup, 1979 (Kidokoro, 1975;Taraskevich & Douglas, 1977;Duffy, Vincent, Fleury, Pasquier, Gourdji & Tixier-Vidal, 1979;Ozawa & Kimura, 1979). Recently it was shown that dopamine has an inhibitory effect on the spontaneous spike frequency of cells in the pars intermedia of the pituitary gland.…”
Section: Effect Of Cocl2contrasting
confidence: 53%
See 2 more Smart Citations
“…Part of this discrepancy between adrenaline output and level of depolarization may be due to the Ca permeability of the ACh receptor channel (Douglas, Kanno & Sampson, 1976b;Douglas & Rubin, 1963). If this is the case then this is in contrast to results obtained from an adrenal chromaffin cell line where stimulation of catecholamine secretion (Ritchie, 1979) by cholinergic agonists is predominantly due to Ca influx through the voltage dependent Ca channel (Stallcup, 1979 (Kidokoro, 1975;Taraskevich & Douglas, 1977;Duffy, Vincent, Fleury, Pasquier, Gourdji & Tixier-Vidal, 1979;Ozawa & Kimura, 1979). Recently it was shown that dopamine has an inhibitory effect on the spontaneous spike frequency of cells in the pars intermedia of the pituitary gland.…”
Section: Effect Of Cocl2contrasting
confidence: 53%
“…Stimulation by ACh may additionally involve Ca influx through the ACh receptor channel (Douglas & Rubin, 1963). However, in physiological salt concentrations this appears to be a minor pathway (Stallcup, 1979; Ritchie, 1979), at least in the adrenal medullary cell line studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). A consider able part of nicotine-evoked catecholamine-re lease depends on Ca-influx mediated through Ca channels secondly activated by depolariza tion in PC12 cells (22,23). Thus, the potent inhibition by hirsutine of the dopamine-release may be due to blockade by hirsutine of Ca channels (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…5A) was not largely affected by 10 pM hirsuteine. A con siderable part of the nicotine-evoked catecholamine re lease depends on Ca-influx mediated through Ca channels secondarily activated by depolarization in PC 12 cells (22,23). Although hirsuteine (1-10 pM) inhibited Ba currents (Fig.…”
Section: Discussionmentioning
confidence: 99%